Who Is Your Perfect Match? Educational Norms, Educational Mismatch and Firm Profitability - Stephan Kampelmann; Benoît Mahy; François Rycx; Guillaume Vermeylen (Institute for the Study of Labor (IZA), 2016)
We provide first evidence regarding the direct effect of educational norms and educational mismatch on the bottom line of firms across work environments. To do so, we use rich Belgian linked employer-employee panel data, rely on the methodological approach pioneered by Hellerstein et al. (1999), and estimate dynamic panel data models at the firm level. Our findings show an 'inverted L' profitability profile: undereducation is associated with lower profits, whereas higher levels of normal and overeducation are correlated with positive economic rents of roughly the same magnitude. The size of these effects is amplified in firms experiencing economic uncertainty or operating in high-tech sectors.
Keywords: J21; J24; 330; educational mismatch; productivity-wage gaps; linked panel data